Obstacles to Investment in Iraq (Entrepreneurship Journal for Finance and Business, 2024)
Creating the right environment is one of the most important factors for attracting capital and investors. Also, the requirements that attract investment may be related to such as the availability of manpower, natural resources and market needs, and these are present in Iraq. There are requirements that the state must provide through appropriate legislation and laws, which require clarity and simplification, in addition to security and political stability because the capital operates in safe and stable conditions. Investment is of great importance to the Iraqi economy, for its role in the development and transfer of technology and modern technologies to contribute to the development of Iraq, increase and diversify its production base, and bypass the unilateral aspect that depends entirely on the export of crude oil, there are some obstacles that still remain and need to be resolved. Some obstacles to foreign investment in Iraq. The objective of the study is knowing the obstacles of the Iraqi investment environment